Impact of cell wall polysaccharide modifications on the performance of Pichia pastoris: novel mutants with enhanced fitness and functionality for bioproduction applications. - Cheng B; Yu K; Weng X; Liu Z; Huang X; Jiang Y; Zhang S; Wu S; Wang X; Hu X (BioMed Central Ltd, 2024)
BACKGROUND: Pichia pastoris is a widely utilized host for heterologous protein expression and biotransformation. Despite the numerous strategies developed to optimize the chassis host GS115, the potential impact of changes in cell wall polysaccharides on the fitness and performance of P. pastoris remains largely unexplored. This study aims to investigate how alterations in cell wall polysaccharides affect the fitness and function of P. pastoris, contributing to a better understanding of its overall capabilities. RESULTS: Two novel mutants of GS115 chassis, H001 and H002, were established by inactivating the PAS_chr1-3_0225 and PAS_chr1-3_0661 genes involved in β-glucan biosynthesis. In comparison to GS115, both modified hosts exhibited a looser cell surface and larger cell size, accompanied by faster growth rates and higher carbon-to-biomass conversion ratios. When utilizing glucose, glycerol, and methanol as exclusive carbon sources, the carbon-to-biomass conversion rates of H001 surpassed GS115 by 10.00%, 9.23%, and 33.33%, respectively. Similarly, H002 exhibited even higher increases of 32.50%, 12.31%, and 53.33% in carbon-to-biomass conversion compared to GS115 under the same carbon sources. Both chassis displayed elevated expression levels of green fluorescent protein (GFP) and human epidermal growth factor (hegf). Compared to GS115/pGAPZ A-gfp, H002/pGAPZ A-gfp showed a 57.64% higher GFP expression, while H002/pPICZα A-hegf produced 66.76% more hegf. Additionally, both mutant hosts exhibited enhanced biosynthesis efficiencies of S-adenosyl-L-methionine and ergothioneine. H001/pGAPZ A-sam2 synthesized 21.28% more SAM at 1.14 g/L compared to GS115/pGAPZ A-sam2, and H001/pGAPZ A-egt1E obtained 45.41% more ERG at 75.85 mg/L. The improved performance of H001 and H002 was likely attributed to increased supplies of NADPH and ATP. Specifically, H001 and H002 exhibited 5.00-fold and 1.55-fold higher ATP levels under glycerol, and 6.64- and 1.47-times higher ATP levels under methanol, respectively, compared to GS115. Comparative lipidomic analysis also indicated that the mutations generated richer unsaturated lipids on cell wall, leading to resilience to oxidative damage. CONCLUSIONS: Two novel P. pastoris chassis hosts with impaired β-1,3-D-glucan biosynthesis were developed, showcasing enhanced performances in terms of growth rate, protein expression, and catalytic capabilities. These hosts exhibit the potential to serve as attractive alternatives to P. pastoris GS115 for various bioproduction applications.
Keywords: ATP; Carbon conversion ratio; Cell wall; Ergothioneine; Human epidermal growth factor; Pichia pastoris; S-adenosyl-L-methionine; Unsaturated lipids; β-1,3-D-glucan synthase; Humans; Pichia; Methanol; Glycerol; Adenosine Triphosphate; Carbon; Cell Wall; Polysaccharides; Recombinant Proteins; Saccharomycetales